Calling Your Aunt Bertha for Social Assets: Family Medicine and Social Determinants of Health - Nick DeVetter; John M. Westfall; Mark Carrozza; Erin Westfall (SAGE Publishing, 2022)
Purpose: The sociopolitical determinants of health drive health outcomes and inequities in the United States. Primary care practices are, increasingly, expected by payers and policy makers to assess patients' social needs. Resource referral platforms provide physicians with information and referral systems for community resources. One commonly used platform is Aunt Bertha/Find Help (AB/FH). The American Academy of Family Physicians (AAFP) Neighborhood Navigator (NN) tool allows physicians and laypeople to search for resources using AB/FH. We sought to describe what users were searching for and to identify patterns to inform resource allocation. Methods: This was a descriptive study of the AAFP's NN tool. Searches of NN were analyzed to describe what users were searching for. Results: From 2018 to April 2022 there were 168 135 searches. The most common searches were for food and housing insecurity (22%, 21%) and health care referral (20.6%) with 22% more searches in the winter than the spring. There was a 119% increase in searches between 2018 and 2022, and a 47% increase in searches during the COVID-19 Pandemic. In the "Health" category the top 20 subcategories accounted for over 77% of searches. Conclusions: Family physicians and their patients use NN to search AB/FH for community resources to address adverse social determinants of health (SDOH). As expected, searches increased during the COVID-19 pandemic. This type of analysis may help individual clinicians, practices, and health systems prepare for the most common social needs of their patients. Social resource platforms might serve as a robust measure for primary care practice screening and referral for SDOH.